Developmental and hormonal regulation of Arabidopsis thaliana ornithine-delta-aminotransferase - A. A. Egorova; S. V. Gerasimova; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Ornithine aminotransferase (OAT) catalyzes transfer of the delta-amino group from L-ornithine to oxo-glutarate. In plants, this reaction biochemically connects urea cycle, proline cycle, and polyamine biosynthesis pathway. OAT activity is shown to be associated with biotic and abiotic stress responses and nitrogen metabolism, but its physiological role is still unclear. In our study, we decided to investigate transcriptional regulation of the OAT gene in Arabidopsis thaliana under normal conditions and in response to various growth regulators. In the present work, the reporter gene construct containing the Escherichia coli β-glucuronidase gene (gus) under control of the A. thaliana OAT gene promoter was introduced into the genome of A. thaliana ecotype Columbia plants using the floral dip method; GUS activity was assayed in different experimental conditions including hormone treatment, low and high nitrogen and salinity. The GUS activity was analyzed histochemically. Plants were incubated with staining solution containing X-Gluc. We show that under standard growth conditions, the promoter is active during germination and in developing floral organs. OAT promoter activity specifically activates in response to different forms of auxin (IAA, NAA, and 2,4D), cytokinin (6- BAP), ethylene precursor (ACC), high nitrogen and salinity. Analysis of the OAT expression by qRT-PCR confirmed the pattern observed using the GUS reporter system. The OAT gene showed a significantly elevated expression in fourday- old seedlings and in plant roots in response to auxins and cytokinins. The analysis of the OAT promoter structure reveals cis-acting regulatory DNA elements associated with auxin regulation and abiotic stresses. The results of the study indicate that the OAT gene is involved in developmental processes and is regulated by auxin and cytokinins.